Trends in the Population Prevalence of People Who Inject Drugs in US Metropolitan Areas 1992–2007 - Tempalski, Barbara (Public Library of Science, 2013)
BACKGROUND: People who inject drugs (PWID) have increased risk of morbidity and mortality. We update and present estimates and trends of the prevalence of current PWID and PWID subpopulations in 96 US metropolitan statistical areas (MSAs) for 1992–2007. Current estimates of PWID and PWID subpopulations will help target services and help to understand long-term health trends among PWID populations. METHODOLOGY: We calculated the number of PWID in the US annually from 1992–2007 and apportioned estimates to MSAs using multiplier methods. We used four types of data indicating drug injection to allocate national annual totals to MSAs, creating four distinct series of component estimates of PWID in each MSA and year. The four component estimates are averaged to create the best estimate of PWID for each MSA and year. We estimated PWID prevalence rates for three subpopulations defined by gender, age, and race/ethnicity. We evaluated trends using multi-level polynomial models. RESULTS: PWID per 10,000 persons aged 15–64 years varied across MSAs from 31 to 345 in 1992 (median 104.4) to 34 to 324 in 2007 (median 91.5). Trend analysis indicates that this rate declined during the early period and then was relatively stable in 2002–2007. Overall prevalence rates for non-Hispanic black PWID increased in 2005 as compared to other racial/ethnic groups. Hispanic prevalence, in contrast, declined across time. Importantly, results show a worrisome trend in young PWID prevalence since HAART was initiated – the mean prevalence was 90 to 100 per 10,000 youth in 1992–1996, but increased to >120 PWID per 10,000 youth in 2006–2007. CONCLUSIONS: Overall, PWID rates remained constant since 2002, but increased for two subpopulations: non-Hispanic black PWID and young PWID. Estimates of PWID are important for planning and evaluating public health programs to reduce harm among PWID and for understanding related trends in social and health outcomes.